Geochemistry, provenance, and tectonic setting of Paleoproterozoic metasedimentary and metavolcanic units of the Estonian Alutaguse region, eastern Fennoscandia - Juan David Solano-Acosta; Alvar Soesoo; Rutt Hints (Estonian Journal of Earth Sciences)
This research focuses on the geochemical analysis of Paleoproterozoic metasedimentary and metavolcanic units in the Alutaguse region of northern Estonia, shedding light on the geodynamic evolution during the Svecofennian orogeny in eastern Fennoscandia. The metasedimentary units consist of micaceous gneisses (± Grt ± Crd ± Sil), and the metavolcanic units include amphibolites and pyroxenic gneisses. Geochemical analyses utilized both historical and new whole-rock geochemical data. Weathering indices indicated their applicability for provenance studies and tectonic setting analyses. Metasediments are classified by their silica content: high-SiO2 (>63 wt%) metasediments resemble litharenites, implying higher maturity and felsic origins akin to the upper continental crust reference; low-SiO2 (